Diametrical and Axial Indirect Tensile Testing Using H-Ometer on a Weak Rock Model and Its Finite Element Simulation - Ahmad, Juraidah (2001)
A method of testing for the tensile strength of weak rock from H-Ometer is presented. H-Ometer tests are carried out on artificial weak rock specimen to test for the accuracy of the model. The weak rock is a simulation of weakly cemented sandstone, which is assumed homogeneous and isotropic and contains no discontinuities. Presently, the existing method of in direct tensile testing using the H-Ometer test is carried out on diametrical specimen model. In this study, efforts to determine a suitable method of testing are carried out on both axial and diametrical model position. The test was conducted on both model specimens, which is subjected to incremental load until failure occurs, and at each load response, the deformation, crack pattern and tensile strength were determined. In this study, a 3-Dimensional elasto-plastic analysis of the experimental work using commercially available LUSAS Finite Element Method is carried out to simulate the performance of H-Ometer on both axial and diametrical model specimens. The ability of the simulated models to predict the tensile strength and crack pattern from H-Ometer will validate the experimental results. Comparison of results for both diametrical and axial model specimen will determine the appropriate model specimen that will give accurate results from H-Ometer test. Throughout this investigation, results of both model specimens carried out using H-Ometer testing device is found to be reliable with indirect tensile strength values ranging from 0.256 MPa to 0.218 MPa. As for the numerical analysis, tensile strength results of both models differ by 1.3%, which is almost negligible and indicates that ideally, either testing position is appropriate. However, experimentally, the axial model agreed more closely to the finite element analysis, which differs by 3.6% compared to 11.3% for the diametrical model.